Precipitation hardened martensitic stainless steel for press plates, its solution treated material and aging treated material
Patent Information
- Application Number
- JP2024176434
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2044-10-08
Smart Images

Figure 0007633464000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a precipitation hardened martensitic stainless steel capable of providing a press plate having high hardness and excellent flatness, and to a solution treated material and an aged material thereof. [Background technology]
[0002] For press plates used in press-forming laminates such as multilayer printed wiring boards, precipitation-hardened martensitic stainless steels such as SUS630 are used, which can achieve high strength by adding Cu to precipitate the ε-Cu phase.
[0003] For example, in Patent Document 1, in addition to the ε-Cu phase, Ti and Si are added to form Ni 16 A precipitation-hardened martensitic stainless steel has been disclosed in which the Ti6Si7-based intermetallic compound phase (G phase) is controlled to be distributed within the crystal grains, thereby maintaining high strength and toughness. The G phase that precipitates by aging heat treatment, that is, Ni 16 Since X in X6Si7 can be substituted not only with Ti but also with Fe, Mn, and Nb, we have clarified the composition by adjusting the amount of Nb in particular.
[0004] Patent Document 2 discloses a manufacturing method and steel material for a press plate in which austenitic stainless steel with a high austenite ratio containing 1.0 to 4.0 mass% Si is subjected to necessary shape modification and then aging treatment to increase the surface hardness to 430 HV or more by strain aging. It points out that it is difficult to sufficiently flatten a steel plate made of hard stainless steel with a surface hardness of 400 HV or more by shape modification alone using temper rolling or a tension leveler, and that when martensitic stainless steel is used, flatness cannot be ensured in the quenching or tempering process, and it states that an austenitic stainless steel with little martensite and a high austenite ratio should be used. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2021-134395 A [Patent Document 2] JP 2008-297601 A Summary of the Invention [Problem to be solved by the invention]
[0006] Meanwhile, in the case of precipitation hardening martensitic stainless steel such as SUS630, a specified hardness (strength) is obtained by carrying out solution treatment at 1000° C. or higher and then aging treatment at a temperature of about 500° C. In other words, precipitation hardening martensitic stainless steel for press plates is required to have a hardness that allows shape modification after solution treatment, while also being able to increase the strength to a sufficient hardness by the subsequent aging treatment.
[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a precipitation hardened martensitic stainless steel, a solution treated material and an aging treated material thereof, which are capable of providing a press plate having high hardness and excellent flatness. [Means for solving the problem]
[0008] The precipitation hardening martensitic stainless steel for press plates of the present invention has a composition, in mass%, of C: 0.01 to 0.07%, Si: 0.05 to 2.25%, Mn: 0.5 to 5.0%, Ni: 4.5 to 10.0%, Cr: 10.0 to 17.0%, Mo: 0.1 to 1.50%, Cu: 0.30 to 5.0%, Al: 0.001 to 0.100%, N: 0.001 to 0.020%, Ti: 0.15 to 0.55%, Nb: 0.15 to 0.45%, Co: 0.03 to 0.80%, P: 0.04% or less, S: 0.0020% or less, with the balance being Fe and unavoidable impurities, and the composition is expressed as follows, when the mass% of element M is [M]: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 The MA defined as is in the range of 1.0 to 4.5, and H=[Cu]+0.6×[Ni]+1.8×[Si]+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) The present invention is characterized in that H defined by the above is in the range of 5.0 or more.
[0009] According to such features, it is possible to obtain a press plate having high hardness and excellent flatness through solution treatment and aging treatment.
[0010] Further, the solution treated material of the precipitation hardened martensitic stainless steel for press plates according to the present invention has a composition, in mass%, of C: 0.01-0.07%, Si: 0.05-2.25%, Mn: 0.5-5.0%, Ni: 4.5-10.0%, Cr: 10.0-17.0%, Mo: 0.1-1.50%, Cu: 0.30-5.0%, Al: 0.001-0.100%, N: 0.001-0.020%, Ti: 0.15-0.55%, Nb: 0.15-0.45%, Co: 0.03-0.80%, P: 0.04% or less, S: 0.0020% or less, with the balance being Fe and unavoidable impurities, and the composition is expressed as follows, when the mass% of element M is [M]: H=[Cu]+0.6×[Ni]+1.8×[Si]+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) The steel sheet is characterized in that H, defined as above, is in the range of 5.0 or more, the steel sheet has a dual-phase structure of martensite phase + retained austenite phase, the amount of the retained austenite phase is 0.2 to 8 volume %, and the steel sheet has a hardness of less than 380 HV.
[0011] According to such a feature, shape correction can be easily performed, and high hardness can be imparted through aging treatment, making it possible to provide a press plate that has high hardness and excellent flatness.
[0012] In the above-mentioned invention, the composition is as follows, when the mass% of element M is [M]: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 The present invention may be characterized in that the MA, defined as: is in the range of 1.0 to 4.5. According to this feature, it is possible to easily correct the shape, and to impart high hardness through aging treatment, thereby making it possible to provide a press plate having high hardness and excellent flatness.
[0013] Further, an aged material of the precipitation hardening martensitic stainless steel for press plates according to the present invention has a composition, in mass%, of C: 0.01-0.07%, Si: 0.05-2.25%, Mn: 0.5-5.0%, Ni: 4.5-10.0%, Cr: 10.0-17.0%, Mo: 0.1-1.50%, Cu: 0.30-5.0%, Al: 0.001-0.100%, N: 0.001-0.020%, Ti: 0.15-0.55%, Nb: 0.15-0.45%, Co: 0.03-0.80%, P: 0.04% or less, S: 0.0020% or less, with the balance being Fe and unavoidable impurities, and the composition is expressed as follows, when the mass% of element M is [M]: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 The material is characterized in that it has an MA, defined as the above, in the range of 1.0 to 4.5 and a hardness of 450 HV or more.
[0014] According to these features, it is possible to provide a press plate that has high hardness and excellent flatness.
[0015] The composition of the composition is as follows, where the mass% of element M is [M]: H=[Cu]+0.6×[Ni]+1.8×[Si]+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) According to this feature, it is possible to provide a press plate having high hardness and excellent flatness. [Brief description of the drawings]
[0016] [Figure 1] 1 is a list of chemical compositions of steels used in the test. [Diagram 2] 1 is a table showing test results. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] As described above, it is required that a precipitation hardened martensitic stainless steel for press plates has a relatively low hardness after solution treatment, while being able to obtain sufficient hardness after aging treatment. The inventors have conducted extensive research into the effect of adding Co together with Nb to martensitic stainless steel that provides such hardness, and have found that it is possible to obtain the desired hardness both after solution treatment and aging treatment by adjusting the steel composition so that the austenite phase remains after solution treatment. The composition of such a steel may be as follows:
[0018] That is, the precipitation hardening martensitic stainless steel for press plates according to this embodiment has a composition, in mass%, of C: 0.01-0.07%, Si: 0.05-2.25%, Mn: 0.5-5.0%, Ni: 4.5-10.0%, Cr: 10.0-17.0%, Mo: 0.1-1.50%, Cu: 0.30-5.0%, Al: 0.001-0.100%, N: 0.001-0.020%, Ti: 0.15-0.55%, Nb: 0.15-0.45%, Co: 0.03-0.80%, P: 0.04% or less, S: 0.0020% or less, and contains Co together with Nb.
[0019] Furthermore, the composition of the composition is as follows, where the mass% of element M is [M]: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr] +0.25×[Mo]+0.35×[Cu] +30.6×([C]+[N])-16.5 The MA defined as above is in the range of 1.0 to 4.5, and H=[Cu]+0.6×[Ni]+1,8×[Si]+3.8×[Ti] +1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) H defined as above is set to be in the range of 5.0 or more.
[0020] Here, it was found that the composition containing only a small amount of Co together with the above-mentioned Nb can make the difference in hardness before and after aging treatment sufficiently large, and can stabilize the hardness before aging treatment, i.e., after the solid solution treatment, to a hardness that allows shape correction. Although Co is an element that stabilizes the austenite phase, the above-mentioned MA value is an index of the stabilization of the austenite phase for this small amount of Co. By setting the MA value within the above-mentioned range, the amount of residual austenite (residual γ phase) after the solid solution treatment can be kept at an appropriate amount, and the hardness after the solid solution treatment can be relatively low, and excellent flatness can be obtained by shape correction of the sheet material. Incidentally, Co is relatively more contained in the ε-Cu phase than in the G phase, and affects the precipitation form of the compound. The above-mentioned H value is an index of the hardness obtained after aging treatment, but the range of the H value is determined taking into consideration the precipitation form of the compound for the addition of this small amount of Co. By setting the H value within the above-mentioned range, it is possible to obtain a sufficient hardness by aging treatment from the hardness that allows shape correction. In other words, by adding a small amount of Co, the mechanical strength of the base material consisting of the martensite phase is increased, and the mechanical strength of the aged material can be maintained high despite the presence of the austenite phase.
[0021] The material after solution treatment is required to have a two-phase structure of martensite phase + retained austenite phase, with the amount of retained austenite phase being 0.2 to 8% by volume, and a hardness of less than 380 HV. To obtain such a solution treated material, the MA value is in the above-mentioned range of 1.0 to 4.5, preferably in the range of 1.2 to 3.5, and more preferably in the range of 1.4 to 2.5.
[0022] Furthermore, the aged material is required to have a hardness of 450HV or more. To obtain such an aged material, the value of H is in the above-mentioned range of 5.0 or more, preferably in the range of 6.0 to 15.0, and more preferably in the range of 7.0 to 12.0. The upper limit of the value of H is preferably set so as to prevent embrittlement of the steel material during manufacturing.
[0023] The press plate in this embodiment can be manufactured by the following method. First, the steel having the above-mentioned composition is cast, hot rolled, and then cold rolled to obtain a strip steel material of a predetermined thickness. The obtained strip steel material is subjected to a solution treatment, and is transformed into martensite while leaving a part of the austenite phase during cooling. In the solution treatment, the material is held at a predetermined temperature within a range of, for example, 1000 to 1150°C, and then water-cooled. This makes it possible to obtain a solution-treated material of precipitation-hardened martensitic stainless steel for press plates.
[0024] Next, the strip steel material that has become the solution treated material is subjected to shape correction. For example, a tension leveler can be suitably used for shape correction. By setting the hardness of the solution treated material to be less than 380 HV as described above, the burden of the manufacturing process in shape correction can be relatively small. For example, excellent flatness can be obtained only by shape correction using a tension leveler.
[0025] Finally, the steel plate is aged to obtain a predetermined hardness. The aging treatment can be, for example, held at 400 to 600°C for 30 minutes to 10 hours. This allows the hardness after aging to be 450HV or more as described above. This allows an aged material of precipitation hardened martensitic stainless steel for press plates to be obtained.
[0026] In this manner, a press plate having high hardness and excellent flatness can be obtained.
[0027] [Tests on solution treated and aged materials] Next, the results of tests on hardness and other properties of plates made from a number of precipitation hardened martensitic stainless steels will be described.
[0028] For the steels having the composition shown in Examples 1 to 11 and Comparative Examples 1 to 8 in Fig. 1, 20 kg steel ingots were cast, hot forged to obtain forged plates, and cold rolled to obtain steel plates having a thickness of 1.6 mm. The obtained steel plates were solution treated by holding at 1050°C for 2.5 minutes and cooled to obtain solution treated materials. Furthermore, a part of the solution treated materials was shape corrected and aged to obtain aged treated materials.
[0029] As shown in FIG. 2, the Vickers hardness (solution hardness) of the obtained solution treated material was measured, and the amount of the residual γ phase was also measured. The amount of the residual γ phase was measured by EBSD (electron backscatter diffraction) using a FE-SEM (field emission electron microscope; JSM-7001F manufactured by JEOL Ltd.). In addition, the flatness of the solution treated material after shape correction was measured. The flatness was judged from the maximum distance between the top surface of the steel plate and the bottom surface of the ruler by placing a 2m ruler on the top of the steel plate placed on a surface plate. When the distance was 1mm or less, it was judged as "excellent" and recorded as "◎". Similarly, when it was more than 1mm to 3mm or less, it was judged as "good" and recorded as "◯", when it was more than 3mm to 5mm or less, it was judged as "passable" and recorded as "△", and when it was more than 5mm, it was judged as "not good" and recorded as "×". Furthermore, the Vickers hardness (aging hardness) of the aged material was also measured.
[0030] As shown in the figure, for the steels of Examples 1 to 11, the flatness of the solution treated materials after shape correction was all "fair" or better, and the hardness of the aged materials was 450 HV or better. The above-mentioned MA values were in the range of 1.0 to 4.5, the H values were in the range of 5.0 or higher, the residual γ content of the solution treated materials was in the range of 0.2 to 8.0 volume %, and the hardness was 380 HV or less except for Example 1. In Example 1, the hardness of the solution treated material was a relatively high 386 HV, but the flatness was only "fair."
[0031] On the other hand, in Comparative Example 1, the Mn content was smaller than in the Examples, and the MA value was low. In Comparative Example 2, the Ni content was smaller, and the MA value was low. In both cases, the amount of retained γ was small, and the flatness was "bad." It is believed that the small amount of retained γ made the solution material relatively hard, and the flatness was not improved even by shape correction.
[0032] In Comparative Example 3, the amount of each element in the composition was about the same as in the Examples, but the MA value was large and the H value was small. As a result, the hardness of the aged material was low. It is believed that the increase in the MA value increased the amount of residual γ, which made the hardness of the solution-treated material too low, and the aged material did not have sufficient hardness. In addition, the decrease in the H value is believed to have reduced the precipitation hardening ability during the aging treatment, which is also believed to be one of the reasons why the aged material did not have sufficient hardness.
[0033] In Comparative Example 4, the amount of each element in the composition was similar to that of the Examples, but the value of H was small. As a result, the hardness of the aged material was low. This is thought to be because the solution-treated material had the same hardness as the Examples, but the value of H was small, and the precipitation hardening ability during aging was low.
[0034] In Comparative Example 5, the content of Si was low. As a result, the hardness of the aged material was low. Although the hardness of the solution-treated material was the same as that of the Examples, it is believed that the low content of Si prevented the material from achieving sufficient hardness through aging treatment.
[0035] Comparative Example 6 contains almost no Co, but the contents of other components and the MA value are almost the same as those of Example 7. Comparative Example 6 has almost the same solution hardness as Example 7, but the aging hardness is low. In other words, it was found that the Co content of Example 7 was an amount that had almost no effect on the solution hardness, but contributed greatly to the aging hardness. The same is true for the relationship between Comparative Example 7 and Example 11, and the relationship between Comparative Example 8 and Example 2.
[0036] Thus, the steels of Examples 1 to 11 can impart high hardness to the aged material while imparting a relatively low hardness to the solution-treated material so that excellent flatness can be obtained by shape correction. In other words, it is possible to obtain precipitation-hardened martensitic stainless steels, solution-treated materials thereof, and aged materials thereof that can provide press plates having high hardness and excellent flatness.
[0037] The ranges of the composition of the steels of the present invention, including Examples 1 to 11, are set as follows.
[0038] C is an element that contributes to increasing mechanical strength by dissolving, while stabilizing the austenite phase, suppressing the formation of δ-ferrite at high temperatures and increasing the amount of residual austenite after solution treatment. Therefore, excessive C content reduces the precipitation hardening ability caused by aging treatment. Taking these factors into consideration, C is in the range of 0.01 to 0.07%, preferably 0.02 to 0.06%, and more preferably 0.03 to 0.05%, by mass%.
[0039] Silicon is added for deoxidation and is an important element for generating G phase by aging treatment to obtain mechanical strength. On the other hand, silicon is a ferrite generating element, and if contained in excess, it leads to an increase in δ ferrite phase and deteriorates hot workability. In consideration of these, silicon is in the range of 0.05 to 2.25%, preferably 1.05 to 2.05%, and more preferably 1.35 to 1.85% by mass.
[0040] Mn is an element that stabilizes the austenite phase, and contributes to the formation of retained austenite while suppressing the formation of the δ-ferrite phase. On the other hand, if it is contained in excess, a large amount of austenite phase remains, which reduces the mechanical strength after aging treatment. In consideration of these, the Mn content is within the range of 0.5 to 5.0%, preferably within the range of 0.6 to 4.0%, and more preferably within the range of 0.8 to 3.0%, by mass%.
[0041] Ni is an element that stabilizes the austenite phase, and contributes to the generation of retained austenite while suppressing the generation of δ-ferrite phase, and furthermore, is an important element that contributes to the increase of mechanical strength by generating G phase by aging treatment. On the other hand, if it is contained in excess, a large amount of austenite phase will remain, and the mechanical strength after aging treatment will decrease. In consideration of these, Ni is in the range of 4.5 to 10.0%, preferably 5.5 to 9.0%, and more preferably 6.5 to 8.0%, by mass%.
[0042] Cr is an element necessary to ensure the corrosion resistance of stainless steel, and also contributes to the formation of retained austenite. On the other hand, excessive content of Cr leads to the formation of δ-ferrite phase, which leads to a decrease in hot workability. Taking these factors into consideration, the Cr content is in the range of 10.0 to 17.0%, preferably in the range of 12.0 to 16.0%, and more preferably in the range of 13.0 to 15.0%, by mass%.
[0043] Mo is an element necessary for ensuring the corrosion resistance of stainless steel, and also contributes to the formation of retained austenite. On the other hand, excessive content of Mo leads to the formation of δ-ferrite phase, which leads to a decrease in hot workability. Taking these factors into consideration, Mo is in the range of 0.1 to 1.50%, preferably 0.6 to 1.20%, and more preferably 0.7 to 1.00%, by mass%.
[0044] Cu is an element that stabilizes the austenite phase, and contributes to the generation of retained austenite while suppressing the generation of the δ ferrite phase, and is an important element that generates the ε-Cu phase by aging treatment and contributes to increasing the mechanical strength. On the other hand, if it is contained in excess, a large amount of austenite phase will remain, reducing the mechanical strength after aging treatment. In consideration of these, the Cu content is within the range of 0.30 to 5.0%, preferably within the range of 0.40 to 3.0%, and more preferably within the range of 0.50 to 1.5%, by mass%.
[0045] Al is added for deoxidation and is an effective element for stably containing Nb and Ti, which are easily oxidized and therefore have low yields in the molten metal. On the other hand, if it is added in excess, it inhibits the formation of retained austenite because it increases the martensitic transformation start temperature (Ms point). It also leads to an increase in the δ ferrite phase, which deteriorates hot workability. In consideration of these, the Al content is in the range of 0.001 to 0.100%, preferably 0.002 to 0.060%, and more preferably 0.002 to 0.020%, by mass%.
[0046] N is an element that stabilizes the austenite phase, and contributes to the generation of retained austenite while suppressing the generation of the δ-ferrite phase. On the other hand, if it is contained in excess, a large amount of austenite phase remains, which reduces the mechanical strength after aging treatment. In addition, it mainly forms nitrides with Ti, which cause the starting point of fracture in the press plate. Furthermore, it may change the Ms point and cause slab cracks. In consideration of these, N is in the range of 0.001 to 0.020%, preferably 0.002 to 0.015%, and more preferably 0.003 to 0.010% by mass.
[0047] Ti is an important element that generates the G phase by aging treatment and contributes to increasing mechanical strength. On the other hand, excessive content of Ti causes the generation of δ ferrite phase, resulting in a decrease in hot workability. It may also cause the Ms point to change and cause slab cracking. In consideration of these, Ti is in the range of 0.15 to 0.55%, preferably 0.20 to 0.50%, and more preferably 0.25 to 0.45%, by mass%.
[0048] Nb is an important element that generates the G phase by aging treatment and contributes to increasing mechanical strength. On the other hand, excessive content of Nb generates the δ ferrite phase, which leads to a decrease in hot workability. It may also change the Ms point and cause slab cracking. In consideration of these, the Nb content is within the range of 0.15 to 0.45%, preferably within the range of 0.20 to 0.40%, and more preferably within the range of 0.25 to 0.35%, by mass%.
[0049] Co stabilizes the passive film to improve the corrosion resistance of stainless steel, and as a stabilizing element of the austenite phase, it lowers the Ms point and affects the generation of retained austenite. It also improves the hardenability to increase the mechanical strength of the base material (matrix), thereby ensuring the mechanical strength of the aged material. On the other hand, if it is contained in excess, it generates excessive retained austenite in the solution treatment, making it impossible to obtain sufficient hardness even by aging treatment, and also reducing toughness. In addition, it was observed that Co was contained in large amounts in the ε-Cu phase and in small amounts in the G phase in the plate materials after aging treatment made from the steels of Examples 1 to 11 described above. This revealed that Co affects the precipitation morphology of the ε-Cu phase and the G phase. In consideration of these, Co is in the range of 0.03 to 0.80%, preferably 0.05 to 0.50%, and more preferably 0.06 to 0.30% by mass.
[0050] P is an element that is inevitably mixed into steel, and it segregates at grain boundaries and is concentrated in the final solidified portion during casting, promoting solidification cracking and also causing a decrease in hot workability. Therefore, it is desirable to reduce it as much as possible, but excessive refining leads to an increase in manufacturing costs. Taking these factors into consideration, P is set to 0.04% or less, preferably 0.030% or less, and more preferably 0.025% or less, by mass%.
[0051] S is an element that is inevitably mixed into steel, and forms compounds with Mn to become inclusions, lowering corrosion resistance. Furthermore, it segregates at grain boundaries and lowers hot workability. Therefore, it is desirable to reduce S as much as possible, but excessive refining leads to increased manufacturing costs. Taking these factors into consideration, S is set to 0.0020% or less, preferably 0.0015% or less, and more preferably 0.0010% or less, by mass%.
[0052] Although the representative embodiments of the present invention and modified examples based thereon have been described above, the present invention is not necessarily limited to these, and a person skilled in the art will be able to find various alternative embodiments and modified examples without departing from the spirit of the present invention or the scope of the appended claims.
Claims
1. In mass percent, C: 0.01-0.07%, Si: 0.05-2.25%, Mn: 0.5-5.0%, Ni: 4.5-10.0%, Cr: 10.0-17.0%, Mo: 0.1-1.50%, Cu: 0.30-5.0%, Al: 0.001-0.100%, N: 0.001-0.020%, Ti: 0.15-0.55%, Nb: 0.15-0.45%, Co: 0.03-0.80%, P: 0.04% or less, S: 0.0020% or less, The remainder is Fe and unavoidable impurities. The composition of the composition is as follows, where the mass% of element M is [M]: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 The MA defined by is in the range of 1.0 to 4.5, and H=[Cu]+0.6×[Ni]+1.8×[Si]+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) The present invention relates to a precipitation hardening martensitic stainless steel for press plates, characterized in that H defined by is in the range of 5.0 or more.
2. In mass percent, C: 0.01-0.07%, Si: 0.05-2.25%, Mn: 0.5-5.0%, Ni: 4.5-10.0%, Cr: 10.0-17.0%, Mo: 0.1-1.50%, Cu: 0.30-5.0%, Al: 0.001-0.100%, N: 0.001-0.020%, Ti: 0.15-0.55%, Nb: 0.15-0.45%, Co: 0.03-0.80%, P: 0.04% or less, S: 0.0020% or less, The remainder is Fe and unavoidable impurities. The composition of the composition is as follows, where the mass% of element M is [M]: H=[Cu]+0.6×[Ni]+1,8×[Si]+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) H defined as above is in the range of 5.0 or more, A solution-treated precipitation-hardened martensitic stainless steel for press plates, characterized in that it has a two-phase structure of martensite phase + retained austenite phase, the amount of the retained austenite phase is 0.2 to 8 volume %, and the hardness is less than 380 HV.
3. The composition of the composition is as follows, where the mass% of element M is [M]: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 3. The precipitation hardening type martensitic stainless steel solution material for press plates according to claim 2, characterized in that the MA defined by is in the range of 1.0 to 4.
5.
4. In mass percent, C: 0.01-0.07%, Si: 0.05-2.25%, Mn: 0.5-5.0%, Ni: 4.5-10.0%, Cr: 10.0-17.0%, Mo: 0.1-1.50%, Cu: 0.30-5.0%, Al: 0.001-0.100%, N: 0.001-0.020%, Ti: 0.15-0.55%, Nb: 0.15-0.45%, Co: 0.03-0.80%, P: 0.04% or less, S: 0.0020% or less, The remainder is Fe and unavoidable impurities. The composition of the composition is as follows, where the mass% of element M is [M]: MA=[Ni]+0.65×[Mn]+0.23×[Si]+0.62×[Cr]+0.25×[Mo]+0.35×[Cu]+30.6×([C]+[N])-16.5 The MA defined by is in the range of 1.0 to 4.5, An aging-treated precipitation-hardened martensitic stainless steel for press plates, characterized in that it has a hardness of 450 HV or more.
5. The composition of the components is H=[Cu]+0.6×[Ni]+1.8×Si+3.8×[Ti]+1.8×[Nb]-0.9×[Mn]-13.8×([C]+[N]) 5. The aging-treated precipitation-hardened martensitic stainless steel for press plates according to claim 4, wherein H, defined as: is in the range of 5.0 or more.
Citation Information
Patent Citations
High-strength precipitation-hardening stainless steel used for laminated board and manufacturing method thereof
CN111101081A
Precipitation-hardening type martensitic stainless-steel with high strength superior in corrosion resistance
JP2002161343A
Austenitic stainless steel for press plate
JP2008297601A
Precipitation-hardening martensitic stainless steel
JP2021134395A
Precipitation hardening martensitic stainless steel
WO2012111188A1